ISOLASI CASHEW NUT SHELL LIQUID DARI KULIT BIJI JAMBU METE (Anacardium occidentale L) DAN KAJIAN BEBERAPA SIFAT FISIKO-KIMIANYA - Simpen, I N. (Jurnal Kimia (Journal of Chemistry), 2012)
The research on the isolation of Cashew Nut Shell Liquid (CNSL) from seed husk of cashew nut by solidliquid extraction has been carried out. The extraction used mixture of chlorofom-ethanol (3:1, 1:1, 1:3) and hexaneethanol (3:1, 1:1, 1:3). The extract was analysed for its phisico-chemical properties namely density, viscosity, acidity, and iod number. The extract with highest rendement was analysed by GC-MS (gas cromatography-mass spectrometry) and infrared (IR) spectrophotometer to prove that anacardic was the mayor component of CNSL. The highest rendement (44.38 %) was resulted from the extraction using 3:1 hexane-ethanol. The extract has a density of 0.9352 g/mL, a viscosity of 8.98 pise, acid of 96.94 mg NaOH/g CNSL, and 86.98 g iod/100g CNSL. The GC-MS and IR analyses showed that the major component of CNSL was anacardic acid.
Keywords: isolation, Cashew Nut Shell Liquid (CNSL), cashew nut, extraction